The Literary Facebook: Notes on the Possibilities of Literature in Internet Social Networking - Casocot, Ian Rosales (Silliman Journal, 2022)
Can social networking be a source of literature? This article posits that there is a possibility of Facebook and Twitter becoming a medium for literary expression. While many contemporary Filipino writers consider time spent on social networking sites such as Facebook and Twitter to be “a waste of time,” a growing number of writers have begun looking at the possibilities of the "status update" as a form of literature, akin to the haiku, that is very much a form dictated by the Internet age.